Պղնձի հիմքով դիսպերս կարծրացող և պղնձյա թելքերով ամրանավորված փոշեկոմպոզիտային նյութերի ջերմային մշակման գործընթացի հետազոտումը - Ս. Գ. Աղբալյան; Գ. Ա. Վասիլյան; Ա. Ռ. Սարգսյան (ՀՀ ԳԱԱ հրատ.)
По результатам экспериментальных исследований определены оптимальные параметры упрочняющей термообработки (закалка, старение, которые обеспечивают не только высокие механические свойства, но и высокие теплопроводность и электропроводность. According to the results of experimental studies, the optimal parameters of the hardening heat treatment (hardening, aging), providing not only high mechanical properties, but also high thermal and electrical conductivity.
Keywords: Technology; Mechanical engineering and machinery